The woman in Disney movies. a pedagogical proposal - ROS-GARRIDO, Alicia (2022)
Thi spaper shows a look and a necessary examination about Disney films and the role of women in them, from the traditionally famous with princesses to the more recento nesstarring women with concerns and initiative, who do not need a prince in their lives and in which they decide thei rown destiny. Specifically, it offers a didactic proposal that aims to understand, analyze, reflect and dialogue about the Maleficent film, providing a tool that makes it posible to investigate one of the Disney film tapes that al ready en rapture children of society, the future citizenship. With out realizingit, or perhaps with total premeditation, a patriarcal society continues to be produced and reproduced that through education has to be transformed.